EVALUASI KUALITAS APARAT PENGAWAS INTERN PEMERINTAH DALAM PENGAWASAN KEUANGAN DAERAH (Studi pada Pemerintah Daerah Kabupaten Minahasa Tenggara) - Lumbantobing, Josua H.R.; Mawikere, Lidya (GOING CONCERN : JURNAL RISET AKUNTANSI, 2015)
This study aimed to evaluate the quality of Government Internal Supervisory Apparatus (APIP) Southeast Minahasa Regency. A common problem in this study is the finding of the audit that is not detected by the APIP as internal auditor, but was found by the external auditor, the Supreme Audit Agency (BPK). The method used in this research is descriptive qualitative. As in qualitative research, the authors use the method of in-depth interviews and Forum Group of Discussion with informants who have knowledge related to this research. The results show, that became important points APIP quality analysis Southeast Minahasa Regency are: First, to meet the needs of APIP competent to provide technical guidance, education and ongoing training to improve quality. Second, do not do that too frequent mutation, a mutation that is done must be in accordance with competence. While that is key to improving the quality of APIP is a strong commitment from the Head of Region for the creation of good and clean government to the fulfillment of the budget for APIP by 1% in accordance with the Regulatory applicable to improving the quality of APIP to provide technical guidance and education and training sustainable, adding facilities such as office operational vehicles and other supporting infrastructure.